Hacia una conceptualización humanista fundamental de las instituciones sociales. Estado del arte. (2008)
The initial review of the literature for this study allowed us to recognizefour different philosophical approaches that support the same amountof sociological paradigms. Such paradigms are concurrently present inother human sciences that deal with the topic of social institutions inone way or another. Therefore, after analyzing the topos of the notioninstitution, and with the intention of distinguishing this notion, wesynthetically analyze the conceptualizations of institution as proposedby the following approaches: empirical-positivist, critical-dialectic,hermeneutical-existential, and metaphysical-realistic